Study the Effect of Nano-Al2O3 and Fiber Glass on Mechanical and Physical Properties of PMMA Composites for Prosthetic Denture - Qahtan Hamad (Engineering and Technology Journal, 2018)
In the present research, investigate the effect of adding some reinforcing materials which include nano-aluminum oxide (nano-Al2O3) particles that added with different volume fractions of (1%, 2%, 3% and 4%), and random fiber glass that added with fix volume fractions of (4%), into the PMMA matrix as new cold cure resin, and study some mechanical and physical properties of these hybrid laminated composite as prosthesis denture base material. Specimens’ of this project were prepared by using (Hand Lay-Up) method to form a hybrid laminated composites materials. The mechanical tests were performed on these specimens include (tensile test, impact test, flexural test and hardness test), while the physical test was thermal behavior test. Results of this study showed the values of (tensile strength, hardness, thermal conductivity and thermal diffusivity) properties increased when adding the (nano-Al2O3) particles in PMMA composite materials for prosthetic denture base materials. While, the values of impact strength and flexural strength properties were decreased.